Aerobic metabolic trichloroethene biodegradation under field-relevant conditions. (15th March 2019) - Gaza, Sarah; Schmidt, Kathrin R.; Weigold, Pascal; Heidinger, Michael; Tiehm, Andreas
Abstract: Chloroethenes belong to the most widely distributed groundwater contaminants. Since 2014, it has been known that trichloroethene (TCE) can be degraded aerobically and metabolically as growth substrate by a mixed bacterial enrichment culture (named SF culture). In this study, the degradation capabilities under a range of field-relevant conditions were investigated in fixed-bed reactors as well as in batch experiments. Aerobic metabolic TCE degradation was stable over the long term, with degradation optima at 22 °C and pH 7. Degradation of up to 400 μM TCE was observed. The longest starvation period after which degradation of TCE was regained was 112 days. The possible co-contaminants perchloroethene, trans -1, 2-dichloroethene, and cis -1, 2-dichloroethene did not inhibit TCE degradation, even though they were not degraded themselves. The presence of equimolar amounts of 1, 1-dichloroethene and vinyl chloride inhibited TCE degradation. Experiments with groundwater from different chloroethene-contaminated field sites proved the potential of the SF culture for bioaugmentation. Thus, aerobic metabolic TCE degradation should be considered as a promising method for the bioremediation of field sites with TCE as the main contaminant. Graphical abstract: Image 1 Highlights: Field applicability of aerobic metabolic TCE degradation. Long-term stability of aerobic metabolic TCE degradation in fixed-bed reactors. TCE-degrading bacteria are suitable for bioaugmentation. Growth characteristics: pH 5–7, temperature 7–27 °C, up to 400 μM TCE degradable.